Strategic planning models adjusted to network organizations and collaborative work: application to a real case (UNED Research Journal, 2019)
Introduction: planning for network organizations and collaborative work is novel and there are few Latin America studies on this subject. Objective: to analyze strategic planning models that achieve a network organization and collaborative work, and compare with a real case in a Latin American university. Methods: bibliographic review of journals, books and internet sites. Results: although there is a variety of strategic plans for network organizations and collaborative work, flexibility is a common factor. Conclusion: the organization studied fulfills the requirement of flexibility pattern, despite functioning within a hierarchical and less flexible institution.
Keywords: strategic planning; planning models; network organizations; collaborative work